The effects of technology supported brain breaks on physical activity behaviour among Malay primary school children : a transtheoretical perspective - Rizal, Hussein Mohammad (2020)
Technology supported brain breaks (TSBB) is a web-based structured physical activity video that is specifically designed for school settings and can stimulates student’s health and learning. The purposes of this study are (1) to validate the processes of change, self-efficacy and decisional balance scales of the transtheoretical model (TTM) questionnaire (phase one) and (2) to measure the effects of TSBB on stages of change, decisional balance, processes of change, self-efficacy and physical activity participation among Malay primary school children (phase two). In phase one, the original version of TTM was translated into Malay language using forward and backward translation and validated using confirmatory factor analysis on 381 children (188 males and 193 females) aged between 10 to 12 years old, mean (SD) = 10.94 (0.81). A pilot test by using accelerometer (validity test of the TSBB) was also carried out with 32 children; 16 children in each TSBB and non-TSBB groups. In phase two, a total of 159 male and 163 female children aged 10 to 11 years old, mean (SD) = 10.53 (0.50), were recruited from two schools in Kelantan, Malaysia. Purposive sampling was used to divide the children into intervention (n = 177) and control (n = 145) groups. Children in the intervention group underwent TSSB activity one to three times per week for four months (each session lasting 15-30 minutes) while children in the control group were not involve in the TSBB intervention. Body height and weight measurements, as well as TTM questionnaires and leisure-time exercise scale were administered to all of the children in both groups at pre and post-test. Mixed analysis of variance (ANOVA) was used to analyse significant changes at these two time points. For phase one of the study, the final Malay version of TTM questionnaires for Malay primary school children consisted of 24 items for process of changes, 13 items for selfefficacy and 10 items for decisional balance. In addition, the pilot test had provided good validity of the TSBB. For phase two, mixed ANOVA showed significant interaction effect for; stages of change, F(1, 319) = 7.861, p-value, (ηp2) = 0.005 (0.024); pros, F(1, 316) = 31.311, p-value (ηp2) = 0.001 (0.090); internal feeling, F(1, 312) = 4.692, p-value (ηp2) = 0.031 (0.015) and behavioural process F(1, 313) = 7.312, p-value (ηp2) = 0.007 (0.0023). In addition, cognitive process, F(1, 320) = 5.768, p-value (ηp2) = 0.017 (0.018), behavioural process, F(1, 313) = 5.736, p-value (ηp2) = 0.017 (0.018) and internal feeling, F(1, 312) = 6.050, p-value (ηp2) = 0.014 (0.019) were also significant for time effect. TSBB was successful in improving the progression of physical activity change; improve internal feeling (self-efficacy); cognitive and behavioural changes as well as; heightening perceived benefits towards physical activity. Thus, TSBB should be recommended to be used throughout the schools in Malaysia.